2017
DOI: 10.5603/ait.a2017.0031
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of analgesic effectiveness of three different techniques of single-shot interscalene brachial plexus block using 20 mL of 0.5% ropivacaine for shoulder arthroscopy

Abstract: Background: Shoulder arthroscopic procedures impose a challenge to anaesthesiologists in terms of postoperative analgesia. Proper pain management after arthroscopic procedures improves patient satisfaction and facilitates early rehabilitation. Methods: We performed a randomized, prospective clinical study to assess the influence of anthropometric parameters and IBPB technique on the quality of postoperative analgesia. A total of 106 randomly selected patients of ASA I-III status scheduled for elective shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Based on the evidence of the increasingly relevant deep fasciae role in connection to regional anaesthesiology, and given the growing interest in fascial plane, inter-fascial and nerve blocks, it can be reported that the exact thickness of a patient’s arm and forearm fasciae reduces the risk of nerve damage during these procedures [ 1 ]. Furthermore, understanding the thickness of the brachial and antebrachial fasciae is crucial for the fascial plane blocks, influencing the deposit and spread of local anesthetic, not only in the effectiveness of the blocks (i.e., onset time and area of anesthesia) [ 29 ], but also in the postoperative analgesia [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence of the increasingly relevant deep fasciae role in connection to regional anaesthesiology, and given the growing interest in fascial plane, inter-fascial and nerve blocks, it can be reported that the exact thickness of a patient’s arm and forearm fasciae reduces the risk of nerve damage during these procedures [ 1 ]. Furthermore, understanding the thickness of the brachial and antebrachial fasciae is crucial for the fascial plane blocks, influencing the deposit and spread of local anesthetic, not only in the effectiveness of the blocks (i.e., onset time and area of anesthesia) [ 29 ], but also in the postoperative analgesia [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A different question is whether the addition of nerve stimulation to ultrasound guidance offers any advantage for nerve block procedures. Results appear to be consistent across femoral nerve block [25, 26], interscalene brachial plexus block [27], infraclavicular brachial plexus block [28], and popliteal sciatic nerve block [29] techniques, as data show no difference in block success and/or pain scores. This suggests that for nerve targets that are relatively easy to view, nerve stimulation may not confer an additional advantage when used with ultrasound guidance.…”
Section: Nerve Stimulation Vs Ultrasound For Nerve Localisationmentioning
confidence: 83%
“…This emphasizes the safety of the anesthetic regimen used in this study for intra- and postoperative anesthesia in these patients. The use of ultrasound guidance for the detection of the end of the needle was abandoned on purpose because it was reported to have no impact on the time of duration of the sensory block as compared to ultrasound guidance or dual guidance [23]. Additionally, the procedures were performed by the same anesthesiologist which compensates for a decreased accuracy regarding the site of injection and therefore an increased variability of drug dispersion during the nerve block.…”
Section: Discussionmentioning
confidence: 99%